Keberdayaan Petani dalam Optimalisasi Pematang Sawah di Kecamatan Majalengka Kabupaten Majalengka - Fitria Dwi Ayu Parwati; Rudi Hartono; Oeng Anwarudin (Jurnal Penyuluhan Pertanian, 2020)
Farmers who control pests and diseases chemically. In fact, the spirit of sustainable agriculture aims to use such environmentally friendly materials as biological pest control by using crop crops planted by crops. It aims to analyze the descriptive levels of farmer's empowerment, relevant factors and strategies that can be done to increase farmer's empowerment in the optimization of rice cattle. Research is carried out in Germany magazine magazine holds April to July 2019. Population is an active farm rice farmer in farm groups of 302. The sample prescribed by 77 people is using random sampling cluster technique. Independent variables include farmers' characteristics, government education and support and dependent variables - the farmers' empowerment. The analytical techniques used are descriptive and syntax of rank spearman. Studies show that farmers' empowerment levels in the optimization of rice culture are category. A factor associated with farmer's empowerment in the optimization of farm cattle is formal education, prolonged effort, farmer status, training and government support. A strategy that can be done to increase farmer's empowerment is by increasing government training and support activities.